eWOM : The effect of online review and food quality on the intention to visit a restaurant/ Arnieyantie Abdul Hadi - Abdul Hadi, Arnieyantie; Md Nor, Norfezah; Mohd Karim, Nadia Liana; Zulkafli, Muhammad Shakir; Othman, Nor Adiba (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
The rapid development of the food establishment industry witnessed the online reviews for restaurants becoming a significant tools for restaurant owners to increase their sales, image and customers. Thus, this research is conducted to measure the effect of online reviews on intention to visit restaurants. The study was conducted by distributing a self administered questionnaire involving 156 respondents and analyzed using Statistical Package for the Social Sciences (SPSS) version 20. All variables measured was significantly influence the consumer's intention to visit restaurants, especially in terms of positive online reviews (eWOM), negative online reviews (eWOM) and online food quality reviews. Moreover, the results showed a positive relationship between positive online reviews, negative online reviews and food towards consumer intention to visit restaurant. The result also demonstrated that food quality online reviews was least effected on consumer intention to visit restaurant with lowest correlation value. The study confirmed that the online reviews became crutial in improving the quality of sales, image, food and also service of the restaurant.